Cutaneous manifestations of Rickettsial fever in paediatric age group - V., Somashekar; K., Ravindra (International Journal of Research in Dermatology, 2022)
Background: Rickettsial fever is well known to have various cutaneous manifestations that can help in the probable clinical diagnosis especially in the context of non availability of resources and aid in prompt administration of treatment, hence reducing mortalitiy and morbidity. The main objective of this study was to estimate the prevalence of cutaneous manifestations in patients with a positive Weil-Felix and also to study the plethora of cutaneous manifestations seen in Rickettsial fever. Methods: All the consenting patients admitted in in the Department of Paediatrics below 18 years and with a positive Weil-Felix test were thoroughly screened for cutaneous manifestations. Results: Of the 114 patients screened, 29 children (21.05%) had cutaneous manifestations. The various cutaneous manifestations encountered in the study are erythematous rash, maculopapular rash, petechial rash and cutaneous necrosis. Conclusions: Though cutaneous manifestations was seen in only 21% of the patients with fever, when present it could help in suspecting rickettsial fever in a case of pyrexia of unknown origin.